Dietary patterns during two different training periods in adolescent elite female artistic gymnasts - Garcia Aparicio, A.; Torres Garcia, A.; Alonso Ojembarrena, M.; Garrido Pastor, G. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
Artistic gymnastics is a specialty sport that must be started at an early age to achieve elite status. It is an impact sport that requires both physical (strength, speed and balance) and non-physical (harmony, grace and risk) qualities. Traditionally body image and weight control are areas of concern in this sport. We evaluated food intake of these elite adolescent artistic female gymnasts during two different training periods: preseason (P) and competition (C). We looked for differences in their dietary patterns between the two periods. Methods Subjects were 14 Spanish adolescent gymnasts from the National Team. First evaluation was performed during P on 10 gymnasts calibre age=16.1±1.4yr; ht=151.5±4.5cm; wt=45.5±6.2kg; BMI=19.8±2.0kg/m2; hours training/wk=37.5±2.6. The second evaluation was performed during C on 9 gymnasts calibre age=15.8±1.8yr; ht=150.1±3.1cm; wt=44.4±3.2kg; BMI=19.7±1.0kg/m2; hours training/wk=32.2±2.6. Five from each group were evaluated twice. Diet composition was estimated by food weighing (Mettler- Toledo scale with 1g accuracy) for two 5 day periods. During the same days they completed a 24h activity questionnaire to provide energy expenditure estimation (EER)(1). Results Energy intakes (kcal/d) were similar in P and C, and in both ocasions they were in energy balance. However, we observed significant difference (p<.01) in their EER (kcal/d), 2113±121 (P) and 1814±70 (C), in relation to hours trained/wk (p<.01), and in energy distribution from macronutrients for carbohydrates (CH) and lipids (L) (p<.01). Percentage of energy (%E) from proteins was similar in both periods (P vs. C), but %E from CH increased (49±7% vs. 62±6%) and %E from L decreased (34±8% vs. 20±5%). Moreover, absolute CH and L intakes (g/d) increased and decreased respectively (p<.01) from P to C. This increase in %E from CH had been observed in several meals: lunch (p<.01), dinner (p<.01) and snacks (p<.05), and also, the reduction in %E from L (p<.05, p<.05, p<.01) respectively from P to C. Lower intakes were shown for vitamin E (p<0.01) and K (p<0.05) in C. In both periods vitamin E intake was related (p<.01) to fat intake. Furthermore, we found marginal intakes for several micronutrients in both periods (P vs. C): vitamin E (63% vs. 37%), calcium (86% vs. 91%) and magnesium (85% vs. 68%). Discussion/Conclusion Although energy expenditure and energy intake were balanced in both periods, a trend toward energy restriction from fat intake was observed C in which body composition exigency was extreme. However, the nutritional pattern in C was suboptimal due to marginal intakes (1) of vitamin E and K, calcium and magnesium. The increased CH intake in C included a higher sugar intake that could be associated with stress and anxiety. During C a greater dietary supervision is required to effect changes in diet quality.